Evaluation of Unsignalized Intersection: Case Study Intersection Roundabout Munjul Jl KH. Abdul Halim-Jl Pemuda-Jl Siti Armilah Majalengka - Silpi Naskah Lasti; Mohamad Taufik; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2025)
An unsignalized intersection is defined as a meeting of two or more roads not equipped with red lights or traffic signs to control traffic. Traffic problems in Majalengka Regency must be fixed or resolved in an orderly manner. The survey method was used. The research was carried out for two days in one week, and the calculations used MKJI and PKJI. Based on the results of calculations and research conducted at the unsignalized intersection at the Parapatan Munjul Roundabout connecting the road from the East and West of Jalan KH. Abdul Halim from the South of Jalan Pemuda and the North of Jalan Siti Armilah, it was concluded that the total traffic volume during peak hours, namely on Monday, December 23, 2024, at 07.00 - 08.00 with a value of 1562.35 / hour, therefore indicating a poor level of service. The results of the LOS service level have poor information from the East and West, and South and North have good information. Of the population in Majlengka Regency of less than 1.36 million, it will increase over time and traffic volume will increase.